RESEARCH OF PROPERTIES OF RUBBER PRODUCTS DEPENDING ON TEMPERATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It was found that the deterioration of the properties of rubbers occurs after 5-10 minutes of excessive heating or cooling, which leads to an increase in their aging. To slow down aging in the production of rubber materials, antioxidants and antiagers are introduced into their composition, which break off the oxidation chain reactions or prevent oxygen diffusion into rubber and rubber.